2007
DOI: 10.1227/01.neu.0000298897.38979.07
|View full text |Cite
|
Sign up to set email alerts
|

Concepts and Hypotheses

Abstract: Immune response could play a role in or represent a potential marker of CCM lesion proliferation and hemorrhage or could otherwise contribute to lesion phenotype. The ongoing studies will generate preliminary data for future research aimed at comparing the immune response in quiescent versus clinically aggressive CCM lesions. An oligoclonal immune response shown in this research would stimulate future experiments to identify autoimmune or extrinsic antigenic triggers involved in CCM disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…[22, 27, 28] Consistent with this view, we found that plasma cells were present mainly in specimens that had hemosiderin deposition. However, we cannot draw any conclusion regarding adaptive immune responses to the presence of iron from our small descriptive study.…”
Section: Discussionsupporting
confidence: 84%
“…[22, 27, 28] Consistent with this view, we found that plasma cells were present mainly in specimens that had hemosiderin deposition. However, we cannot draw any conclusion regarding adaptive immune responses to the presence of iron from our small descriptive study.…”
Section: Discussionsupporting
confidence: 84%
“…Shenkar et al reported that immunoglobulin heavy and light chain genes were upregulated with up to 20-fold change in human CCM lesions in comparison to brain AVM and normal superficial temporal arteries [4, 11]. Interestingly, we found that 3 common variants in the immunoglobulin heavy locus ( IGH ) and 5 common variants in the immunoglobulin lambda light chain locus ( IGL ) were associated with either ICH or total lesions.…”
Section: Discussionmentioning
confidence: 58%
“…Our candidate gene list includes: 1) Inflammatory cytokines, as polymorphisms in notably IL1A, IL1B, IL1RN and TNF genes have been previously reported associated with phenotypes of brain vascular diseases, including brain arteriovenous malformations or intracranial aneurysms [1217, 20]; 2) Transforming growth factor-β (TGF-β) and related genes that inhibit TGF-β signaling, reducing the number and size of lesions and vessel leakage in CCM1-deficient mice [10]; 3) Genes that encode proteins expressed or secreted by inflammatory or immune cells (T cells, B cells, monocytes and macrophages) and other related genes coding for proteins involved in immune cell development (i.e., CD14, IFNG, IL5, IL6R, IL8, IL18, IL18R1, IL12A, IL12B, IL2, IL17A, IL23A, NFKB1, MIF and MSR1) as inflammatory or immune cells are present in human CCM lesions [4, 6, 11]; 4) Toll-like receptors genes (TLR1, TLR2, TLR3, TLR4, TLR5, TLR6 and TLR10) as well as COX-2 and Selenoprotein genes as encoded proteins have been reported to be essential in the pathogenesis of cerebral ischemia and the pathologic progression of the disease [2126]; 5) Immunoglobulins and other related genes with altered expression in human CCM lesions (CD247, CD3G, CD68, CD200, GUSP11, HLA-DRB1, IGH, IGJ, IGL, LOC390714, MS4A1 and SDC1) [4, 11]. These genes were classified into the following biological sub-pathways [27, 28]: (a) cytokine signaling; (b) eicosanoid signaling; (c) extracellular pattern recognition; (d) NFKB signaling; (e) selenoproteins; and (f) immune response (see online Suppl.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations